Thermal Properties of Liquid Iron at Conditions of Planetary Cores. Issue 4 (13th April 2022) - Li, Qing; Xian, Jia‐Wei; Zhang, Yigang; Sun, Tao; Vočadlo, Lidunka
Abstract: Thermal properties of iron at high pressures ( P ) and temperatures ( T ) are essential for determining the internal structure and evolution of planetary cores. Compared to its solid counterpart, the liquid phase of iron is less studied and existing results exhibit large discrepancies, hindering a proper understanding of planetary cores. Here we use the formally exact ab initio ab initio thermodynamic integration approach to calculate thermal properties of liquid iron up to 3.0 TPa and 25000 K. Uncertainties associated with theory are compensated by introducing a T ‐independent pressure shift based on experimental data. The resulting thermal equation of state agrees well with the diamond anvil cell (DAC) data in the P ‐ T range of measurements. At higher P ‐ T it matches the reduced shock wave data yet deviates considerably from the extrapolations of DAC measurements, indicating the latter may require further examinations. Moreover, the calculated heat capacity and thermal expansivity are substantially lower than some recent reports, which have important ramifications for understanding thermal evolutions of planetary cores. Using Kepler‐36b as a prototype, we examine how a completely molten core may affect the P ‐ T profiles of massive exoplanets. By comparing the melting slope and the adiabatic slope along the iron melting line, we propose that crystallization of the cores of massive planets proceeds from the bottom‐up rather than the top‐down. Plain Language Summary: Earth‐like planets often possess iron‐dominant cores that are partially or completely molten. The thermal properties of liquid iron are therefore essential to constrain the internal pressure, temperature, and evolution of planets. However, existing studies on the topic are limited and the results exhibit large discrepancies, hindering a proper understanding of planetary cores. Here, we simulate the thermal properties of liquid iron using ab initio ab initio thermodynamics integration, a formally exact free‐energy method that is well suited to determine thermal properties. This method achieves highly accurate results at extreme pressure and temperature conditions. Our results help to constrain the pressure‐temperature profiles and thermal evolutions of Earth‐like planets, from smaller ones such as Mars and Mercury to massive exoplanets where the core pressures may exceed 2 TPa. The calculated heat capacity and thermal expansivity are substantially lower than in previous studies, indicating smaller thermal inertia and more rapid core evolution. Core crystallization in massive planets may proceed from the bottom‐up, in contrast to the smaller terrestrial planets of the Solar System. Key Points: Thermal properties of liquid iron are determined up to 3.0 TPa and 25000 K using the formally exact ab initio thermodynamic integration Temperature of a completely molten core can be twice of a frozen core whereas the core pressures are similar Crystallization of the cores of massive planets proceeds from the bottom‐up rather than the top‐down